Anti-cancer effects of blue-green alga Spirulina platensis, a natural source of bilirubin-like tetrapyrrolic compounds - Koníčková, Renata; Vaňková, Kateřina; Vaníková, Jana; Váňová, Kateřina; Muchová, Lucie; Subhanová, Iva; Zadinová, Marie; Zelenka, Jaroslav; Dvořák, Aleš; Kolář, Michal; Strnad, Hynek; Rimpelová, Silvie; et al. (Annals of hepatology, 2014)
Spirulina platensis is a blue-green alga used as a dietary supplement because of its hypocholesterolemic properties. Among other bioactive substances, it is also rich in tetrapyrrolic compounds closely related to bilirubin molecule, a potent antioxidant and anti-proliferative agent. The aim of our study was to evaluate possible anticancer effects of S. platensis and S. platensis-derived tetrapyrroles using an experimental model of pancreatic cancer. The anti-proliferative effects of S. platensis and its tetrapyrrolic components [phycocyanobilin (PCB) and chlorophyllin, a surrogate molecule for chlorophyll A] were tested on several human pancreatic cancer cell lines and xenotransplanted nude mice. The effects of experimental therapeutics on mitochondrial reactive oxygen species (ROS) production and glutathione redox status were also evaluated. Compared to untreated cells, experimental therapeutics significantly decreased proliferation of human pancreatic cancer cell lines in vitro in a dose-dependent manner (from 0.16 g•L-1 [S. platensis], 60 μM [PCB], and 125 μM [chlorophyllin], p<0.05). The anti-proliferative effects of S. platensis were also shown in vivo, where inhibition of pancreatic cancer growth was evidenced since the third day of treatment (p < 0.05). All tested compounds decreased generation of mitochondrial ROS and glutathione redox status (p = 0.0006; 0.016; and 0.006 for S. platensis, PCB, and chlorophyllin, respectively). In conclusion, S. platensis and its tetrapyrrolic components substantially decreased the proliferation of experimental pancreatic cancer. These data support a chemopreventive role of this edible alga. Furthermore, it seems that dietary supplementation with this alga might enhance systemic pool of tetrapyrroles, known to be higher in subjects with Gilbert syndrome.
Keywords: Animals; Bilirubin; proliferace buněk; vztah mezi dávkou a účinkem léčiva; glutathion; Cell Line, Tumor; Glutathione; Mice, Nude; In Vitro Techniques; rostlinné extrakty; Pancreatic Neoplasms; techniky in vitro; lidé; Antineoplastic Agents; Mice; protinádorové látky; nádory slinivky břišní; Reactive Oxygen Species; transplantace heterologní; Transplantation, Heterologous; myši; xenogenní modely - testy protinádorové aktivity; oxidace-redukce; Dose-Response Relationship, Drug; modely nemocí na zvířatech; Oxidation-Reduction; Cell Proliferation; Disease Models, Animal; reaktivní formy kyslíku; bilirubin; tetrapyrroly; Plant Extracts; Xenograft Model Antitumor Assays; Cell Survival; zvířata; viabilita buněk; Tetrapyrroles; Spirulina; myši nahé; nádorové buněčné linie; Humans